Analyser des pédagogies « différentes » : quelques débats autour des questions de méthode - Yves Reuter (Recherches en Éducation, 2025)
This paper deals with some methodological debates concerning research about “different” pedagogies. These de-bates are generated by a few issues: the analysis of logics that shape these researches, the adequation of these researches with their objectives, the decisions about temporality, the refusal of any methodological sectarism, the criteria and the meanings the actors put on them, as well the particularity of the project and the more or less coher-ence between the stated principles and the pedagogical devices.